Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I'm doing my homework and there are a couple of things that I am having trouble grasping. All my homework asks is that I simplify the exponents. For example: 6^5 * 6^3 = 6^8

There are 2 problems I am unsure on what to do. They have to do with multiplying fractions:

(7^3)^5/6 = 7^5/2 is the answer but I don't understand how they got to that. I know there is a certain example I was shown where you had to get common demonators and such but if I apply that it doesn't turn out well. Same for this problem:

(7^3/5)^5/6 = 7^2

3^5/2 * 3^-2 = 3^1/2

share|cite|improve this question
Use some parentheses. – William Aug 23 '12 at 1:47
up vote 2 down vote accepted

For any $x$, $a$, and $b$.

$(x^a)^b = x^{ab}$.

Hence for the first one, letting $x = 7$, $a = 3$, $b = \frac{5}{6}$, you have

$(7^3)^{\frac{5}{6}} = 7^{3 \cdot \frac{5}{6}} = 7^{\frac{5}{2}}$

For the second letting $x = 7$, $a = \frac{3}{5}$ and $b = \frac{5}{6}$, you have

$(7^{\frac{3}{5}})^{\frac{5}{6}} = 7^{\frac{3}{5} \cdot \frac{5}{6}} = 7^{\frac{3}{6}} = 7^{\frac{1}{2}}$.

For the last one, for any $x$, $a$ and $b$

$(x^a)(x^b) = x^{a + b}$.

Letting $x = 3$, $a = \frac{5}{2}$ and $b = -2$, you have

$(3^{\frac{5}{2}})(3^{-2}) = 3^{\frac{5}{2} + -2} = 3^{\frac{5}{2} + \frac{-4}{2}} = 3^{\frac{1}{2}}$.

share|cite|improve this answer
so from the looks of you you just put 3/1 and cross divided to get 5/2? – Alex Miller Aug 23 '12 at 1:54
@AlexMiller It's a normal arithmetic. $3 \times \frac{5}{6} = 15 \div 6 = \frac{5}{2}.$ – user2468 Aug 23 '12 at 1:56
@AlexMiller That just how to multiply fractions. $3 \cdot \frac{5}{6} = \frac{15}{6} = \frac{5}{2}$. By the way, I have never heard of the term cross divide. – William Aug 23 '12 at 1:58
I see I'm over complicating it, just multiply across, denominator and nominator then simplify. Thanks! – Alex Miller Aug 23 '12 at 1:58

In general, $$(a^b)^c=a^{(bc)}.$$ Let us apply that to your first example. We have $$(7^3)^{\frac{5}{6}}=7^{\left(3\cdot \frac{5}{6}\right)}.$$ But $3\cdot \frac{5}{6}=\frac{5}{2}$.

share|cite|improve this answer

The exponent rules are boookkeeping. You need to keep track of the number of powers being used. For example, $$x^a\cdot x^b = x^{a+b}$$ because there are a total of $a+b$ factors of $x$ here. The other important tool is $$\left(x^a\right)^b = x^{ab}.$$ Again, this is bookkeeping.

Hence, in your example $$\left(7^{3/5}\right)^{5/6} = 7^{{3/5}\cdot{5/6}} = 7^{1/2} = \sqrt{7}. $$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.